Vozes Protagonistas: curando e libertando nas encruzilhadas amazônidas - Soares, Amanda Mendes (Brasil, 2025)
The present study aimed to research and analyze the protagonism of students within the public university, in Lower Amazonas, considering, above all, healing and liberation movements in the learning community. Anchored in the thought of bell hooks, which establishes connections between healing, liberation and the learning community, it is understood that the educational space, in addition to learning, is also a space for education for critical consciousness. Education enables historical subjects to echo their marginal voices and seek, through collective and engagement, the transformation of themselves and reality. In this way, the study sought to understand how the schooling trajectory of women and men at the Federal University of Amazonas, at the Institute of Social Sciences, Education and Zootechnics, takes place. Methodologically, the study considered: research diary, conversations, conversation circles and narrative writing. Thus, nine students were invited to participate in a study group that, over a period of one year, met to talk, read, write, and narrate their life and student stories. The data presented are the perceptions and elaboration of the researcher responsible for the project. Therefore, self-narratives and writings were considered, from the epistemological methodological perspective of (auto)biographical studies in education, self-narratives and black feminist epistemology, with bell hooks as the main theoretical reference. The study records were made in the research diary in the form of narrative writing during conversations, circles and self-writing times of the research participants. They were then transcribed onto the computer and choices were made to emerge in the research work. The study results reveal three important categories: institutional care, Maria cycle, ancestry. These categories allow us to glimpse that the echo of these Amazonian voices, the recognition of their life trajectories and training paths are crucial within the University. This space can be a space of healing and liberation. The counter-hegemonic and counter-colonial University, through liberating, critical and engaged proposals, can create opportunities for the construction of learning communities, where people can in fact be subjects and protagonists of their stories.